(untitled) (Revista Iberoamericana de Bioética, 2025)
This study explores the bioethics and applied ethics training of pediatric palliative care professionals in a tertiary hospital in Spain. Using self-administered questionnaires, ethical perspectives and training for addressing complex decision-making processes are analyzed. Results show a predominance of care and responsibility ethics among participants, alongside limited and uneven bioethics training according to professional profile. Moral distress, the lack of a formal method, and the reliance on intuition and common sense as guides are identified as challenges to maintaining objectivity in practice. The study concludes that continuous, tailored training and the creation of safe, reflective spaces are essential for improving decision-making and reducing moral distress.